Growing greenhouse cut flower in hydro-culture - Lévai, P.; Farkas, Zs. (International Journal of Horticultural Science, 2010)
The importance of hydro-cultural growing is significantly increasing.We have been dealing with the hydro-cultural growing of cut flowers at the Department of Ornamental Plant Growing and Maintenance of Gardens at the College Faculty of Horticulture at Kecskemét College since 1988.We started our experiments by growing carnation in growing establishment without soil then we introduced other species of cut flowers and potted ornamental plants into our research work.